METAPHOR IN ENGLISH MOTIVATIONAL DISCOURSE: IDENTIFICATION, FUNCTIONS AND TRANSLATION-ORIENTED IMPLICATIONS (Ustozlar uchun, 2026)
This paper examines the types and functions of metaphor in english motivational discourse through cognitive and pragmatic lenses. The study aims to identify conceptual and lexical metaphors in motivational texts (book excerpts, blog posts, and speech fragments), classify them by source domains, and highlight translation-oriented challenges related to equivalence. A 50,000-word mini-corpus of contemporary motivational materials was compiled; metaphors were identified using the mipvu procedure and subsequently coded into domains such as journey, struggle, growth, light/darkness, and container. The findings show that metaphor in motivational discourse is not merely decorative: it simplifies abstract ideas, reinforces persuasion, mobilizes action, and fosters proximity between author and audience. From a translation perspective, some metaphors lose their rhetorical force when transferred literally, while others require cultural adaptation or re-metaphorization to preserve pragmatic impact. The paper concludes with practical recommendations for efl pedagogy and translation practice, emphasizing systematic metaphor analysis as a tool for improving comprehension and communicative effectiveness.